Acquisition of the Chinese Demonstratives “zhe” and “na” by Spanish Speakers - Ziwei, Wang; Xiuchuan, Lu; Zhi, Geng (Sinología hispánica. China Studies Review, 2026)
This paper examines the effects of differences in Chinese and Spanish demonstratives on the acquisition of Chinese demonstratives zhè/nà (这/那) by native Spanish speakers, through the analysis of a self-constructed intermediary language corpus, questionnaires, and an interview method in conjunction with a mainstream Chinese textbook in the Spanish-speaking regions. It was found that primary level learners focus their usage on situational deixis, intermediate and advanced level learners mostly use contextual deixis, both of them use grammaticalized deixis. In addition, some typical errors made by primary level speakers, such as the confusion of zhè and nà, zhège (这个) and zhème (这么), zhè/nà and tā (它/他/她), are also made by intermediate and advanced speakers. And their reasons lie in the ignorance of zhè/nà on the part of teachers and Chinese textbooks, and some inappropriate explanations, etc. The results of this study will provide academic references for the teaching of zhè/nà to Spanish speakers, and we also offer suggestions for the design of Chinese textbooks and the teaching in the Spanish-speaking world with respect to demonstratives.